Burn-induced distant organ injury in rats and the effect of minocycline - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2017)
Objectives: This study aimed to examine the anti-inflammatory potential of orally-administered minocycline, a semi-synthetic second-generation tetracycline, on burn-induced liver and kidney damage in rats. Materials and Methods: Female Sprague-Dawley rats (250300 g; n=7-8/group) were used. Burn and sham groups were exposed to 90 C-0 and 25 C-0 water bath for 10 s, respectively. Minocycline (20 mg/kg; twice daily; orogastrically) was administered for 24 h post-burn. After decapitation, trunk blood was collected for biochemical assays. Liver and kidneys were excised for histopathological evaluation and malondialdehyde (MDA), glutathione and chemiluminescence (CL) assays. Results: Minocycline treatment did not exert a significant effect on serum alanine aminotransferase, aspartate aminotransferase, blood urea nitrogen, and creatinine levels of the burn group. Increased serum total oxidant status of the burn group was reversed (P<0.001) and liver microscopic lesion score showed a slight reduction (P<0.01) by minocycline. Minocycline did not cause a significant effect on increased tissue MDA and glutathione levels of the burn group but reversed the elevated luminol CL levels (P<0.001, for liver and P<0.01, for kidney, respectively). Conclusion: Minocycline treatment to rats for 24 h post-burn was found to be effective to reduce oxidant production in the liver and kidney; however, it showed slight protection on these tissues against oxidant damage.
Keywords: Burn; Kidney; Liver; Minocycline; Rat; OXIDATIVE STRESS; LIPID-PEROXIDATION; LUNG; TETRACYCLINES; DOXYCYCLINE; INHIBITION; ISCHEMIA; PROTECTS; TISSUES; LIVER